(untitled) (Triyuga Academic Journal, 2021)
The endangered ethnic community Kusunda primarily resides in the western and mid-western part in Tanahu, Gorkha, Arghakhachi, Kapilwastu, Pyuthan, Rolpa, Dang, and Surkhet districts of Nepal. It is smallest ethnic groups, according to the census of 2011, which has the total number of population 23. But from the field study, they have 151 population and 40 households. Then language, cultural traditions, traditional knowledge and technologies are on the verge of extinction. Now they have been formulating new cultural codes, dress, festivals and trying to adapt to new environment by establishing the relationship to other caste/ethnic groups of Nepal. This article mainly concerns Kusunda people and their relationships to other caste and ethnic groups of Nepal.